Cytokines in Human Health Immunotoxicology, Pathology, and Therapeutic Applications - House, Robert V.; Descotes, Jacques; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2007)
Cytokines in Human Health: Immunotoxicology, Pathology, and Therapeutic Applications explores the role of cytokines in immunotoxicology and human health using a variety of complex methods, from basic research to highly applied therapeutic applications. The first section of the book is devoted to basic concepts of cytokine biology, especially as this relates to the practice of immunotoxicology. Chapters in this section review the ability of external influences to modify the expression, production, and activity of these molecules. The second section provides a broad understanding of the range of cytokine activity in human disease, describing methods for assessing cytokine immunotoxicity. In the third and final section of the book, the increasingly important use of cytokines as therapeutics is explored in detail. This section includes examinations into the effects of cytokines on the immune system and in treating cancer. Timely and comprehensive, Cytokines in Human Health: Immunotoxicology, Pathology, and Therapeutic Applications will serve as both a primer and a starting point for a more detailed investigation of the role these fascinating biological regulators play in human health and disease.
to Cytokines as Targets for Immunomodulation -- Cytokine Measurement Tools for Immunotoxicology -- The Relevance of the T1/T2 Paradigm in Immunotoxicology -- Microbial Exploitation and Subversion of the Human Chemokine Network -- The Use of Cytokines in the Identification and Characterization of Chemical Allergens -- Inflammatory Cytokines and Lung Toxicity -- Cytokine Polymorphisms and Relationship to Disease -- Effects of Drugs of Abuse on Cytokine Responses -- Preclinical Approaches for the Safety Assessment of Cytokines -- Flu-Like Syndrome and Cytokines -- Cytokine-Induced Vascular Leak Syndrome -- Cytokines and Autoimmune Diseases -- Evaluation of Antibodies in Clinical Trials of Cytokines -- Cytokines and Pharmacokinetic Drug Interactions -- Evaluation of the Immunological Effects of Cytokines Administered to Patients With Cancer -- Clinical Adverse Effects of Cytokines on the Immune System.
Keywords: Medicine; Immunology; Pharmacology; Cell biology; Biomedicine; Pharmacology/Toxicology.; Immunology; Cell Biology; Electronic books